Análise teórico-experimental de microrreatores para síntese de biodiesel com recuperação de calor rejeitado - Costa Junior, José Martim (2017)
The present work deals with the analysis of the continuous synthesis of biodiesel in microreactors using the rejected heat of a thermal source and has as objective to obtain the maximum efficiency of the biodiesel production using multiple microreactors, aiming at the scheduling of the production, coupled to micro heat exchangers that allow The utilization of the rejected heat of a secondary process to increase the reaction temperature, and consequent improvement in the conversion rates. The first experimental analysis of the biodiesel synthesis is carried out in a device containing a single metal microreactor built using the micromilling technique and a ethyl esters yield of 92.56% at a residence time of 46.56s was achieved. The other experimental analysis is done in a device composed of multiple metal microreactors coupled to micro heat exchanger, manufactured by the additive manufacturing technique that allows the construction of these components in the same substrate, reducing the thermal resistance of contact. In this device a ethyl ester yield of 99.61% was obtained in a residence time of 34.92 seconds. A diffusive-convective-reactive three-dimensional mathematical model that describes the physico-chemical behavior of the species involved in the biodiesel synthesis is reformulated using the CIEA technique, resulting in a mathematical model non-linear and coupled compound of first-order ODE's which enables for simulations with reduced computational costs. The Markov Chain Monte Carlo method (MCMC) is used to estimate the kinetic constants using real experimental data with low conversion rates, which maximizes the presence of intermediary species, and increases the sensitivity of the problem to the parameters.